An Ontology to support Knowledge Management Solutions for Human-Computer Interaction Design - Castro, Murillo; Barcellos, Monalessa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Developing interactive systems is a challenging task that involves concerns related to the human-computer interaction (HCI), such as usability and user experience. Therefore, HCI design is a core issue to the quality of such systems. HCI design often involves people with different backgrounds (e.g., Arts, Software Engineering, Design). This makes knowledge transfer a challenging issue due to the lack of a common conceptualization about HCI design, leading to semantic interoperability problems, such as ambiguity and imprecision when interpreting shared information. Ontologies have been acknowledged as a successful approach to represent domain knowledge and support knowledge-based solutions. Hence, in this work, we propose to explore the use of ontologies to represent structured knowledge of HCI design and improve knowledge sharing in this context. We developed the Human-Computer Interaction Design Ontology (HCIDO), which is part of the Human-Computer Interaction Ontology Network (HCI-ON) and is connected to the Software Engineering Ontology Network (SEON). By making knowledge related to the HCI design domain explicit and structured, HCIDO helped us to develop KTID, a tool that aims to support capturing and sharing knowledge to aid in HCI design by allowing HCI designers to annotate information about design choices in design artifacts shared with HCI design stakeholders. Preliminary results indicate that the tool can be particularly useful for novice HCI designers.